Marginalisation et intégration dans la cité: éléments pour une lecture dynamique de la pensée politique de la République - Helmer, Étienne (ΠΗΓΗ/FONS, 2017)
It is often assumed that the heart of Plato’s political thought in the Republic addresses the conditions of possibility of the just city. Such a reading then concentrates mostly on the institution of the philosopher-kings, and the tripartite organization of the city. Without being wrong, this reading is however extremely partial and reductive as it obscures the main focus of Plato’s political thought in this dialogue. Far from analyzing only the conditions of possibility of the just city, Plato’s main concern deals with the processes of marginalization and integration of distinct population groups and functions in the city. Three arguments go in this direction. First, both the antagonistic relationships between economy and politics at the first stages of the city (Book II), and the progressive degradation of the regimes as a result of the conflict be-tween these two spheres (Book VIII), invite us to read the Republic as a reflection on politics considered as a socio-economic dynamic, rather than a mere description of the static political and economic structure of the just city. Second, the three functional categories required to build this city are less presented as elements ready to be put at work, than as problematic elements, which are subject to many changes. This is especially true about the philosophers, with respect to their existence, education and preservation. Third, Plato also evokes secondary categories, in the just city and the ordinary cities as well - for instance, the children without talent, the beggars, the incurables - and he wonders about how and how far they can or must be integrated in-to or marginalized from the cities.
Keywords: City; exclusion; integration; marginalization; Plato; Republic